Determinants of Islamic banks’ firm value: empirical evidence from IFSB member countries - Vindi Nur Fitriyah; Guntur Kusuma Wardana (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — The purpose of this research is to determine the effect of profitability, debt policy, dividend policy and capital structure on the firm value of Islamic banks. Method — The population in this study consisted members of Islamic Financial Service Board (IFSB) period 2022, totaling 188 Islamic Financial Institutions. Using the purposive sampling technique, there was 18 Islamic banks that used as a samples with a quarterly time series data from 2021 until 2022. The data used was secondary and analyzed by panel data regression with Eviews10.Result — The results show that partially profitability, dividend policy and capital structure has significant effect on firm value of Islamic banks, but debt policy has no significant effect on firm value of Islamic banks. Meanwhile, simultaneously profitability, debt policy, dividend policy and capital structure have a significant effect on firm value of Islamic banks.Contribution — The main contribution of this research is particular to the firm value literature of Islamic banks, which is useful as a reference and investment decision making for third parties.